1 + 1
2 x 28
32 : 3
433 - 55
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt \(\frac{1}{229}\)= a , \(\frac{1}{433}\)=b ta có:
3a.(2+b) - a.(1-b) - 4ab= 6a+3ab-a+ab-4ab
=5a=5.\(\frac{1}{229}\)= \(\frac{5}{229}\)
\(\frac{29182}{12728}:\frac{2293}{1277}:\frac{3283}{2832}X\left(\frac{8}{16}-\frac{1}{2}\right)\)
~_~
\(\frac{29182}{12728}:\frac{2293}{1277}:\frac{3283}{2832}\cdot\left(\frac{8}{16}-\frac{1}{2}\right)\)
\(=\frac{29182}{12728}:\frac{2293}{1277}:\frac{3283}{2832}\cdot\left(\frac{8}{16}-\frac{8}{16}\right)\)
\(=\frac{29182}{12728}:\frac{2293}{1277}:\frac{3283}{2832}\cdot0=0\)
Bài đây dễ mà :V
\(A=3a\cdot\left(2+b\right)-a\cdot\left(1-b\right)-4ab\)
\(=6a+3b-a+ab-4ab=5a+3b-3ab\)
1 + 1 = 2
2 x 28 = 56
433 - 55 = 378
=^_^=
k mình nha
1 + 1 = 2
2 x 28 = 56
32 : 3 = \(\frac{32}{3}\)
433 - 55 = 378